Exploiting a mouse model to identify the mechanistic basis of resistance / susceptibility to a major gastrointestinal (GI) nematode infection of man and livestock - Dold, Christina (Trinity College (Dublin, Ireland). Department of Zoology, 2010)
Ascaris lumbricoides and Ascaris suum are widespread parasitic nematodes of humans and pigs respectively. Ascaris worms exhibit an overdispersed frequency distribution in their hosts. In addition, observation of re-infection patterns post-chemotherapy has indicated that individuals display a degree of predisposition to their worm burden status. The underlying reasons for the observed variation in worm burden within host populations have yet to be fully defined and are difficult to elucidate in humans and pigs for ethical and logistical reasons. Comparative studies on larval migration demonstrated that the mouse is a suitable model for the early phase of A suum infection. A murine model was recently developed and optimised and two inbred strains were identified as putatively susceptible (C57BL/6j) and resistant (CBA/Ca) to infection. The present study was focused upon the mechanism underlying the generation of resistance and susceptibility to A. suum infection in the mouse model. All experiments conducted involved the comparison of different host parameters in the two different host strains during single-pulse infections.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin